Relevansi Ayat-ayat Al-Qu’ran dengan Konsep Fisika Pada Pembelajaran di Sekolah: Systematic Literature Review - Syahrial Ayub; Naf’atuzzahrah (STAI AL-AMIN, 2026)
This study aims to analyze the relevance of the verses of the Qur'an to the concept of physics in school learning through a Systematic Literature Review (SLR) approach. This study is motivated by the importance of integration between science and Islamic values ​​in learning to shape students who not only have academic competence, but also religious character and critical thinking skills. The research method uses SLR with reference to the PRISMA stages which include identification, screening, eligibility, and inclusion. Data sources were obtained from the Scopus and Google Scholar databases through the Publish or Perish application with a publication range of 2015–2025. The article selection process resulted in 10 articles that met the inclusion criteria for qualitative descriptive analysis. The results show that the verses of the Qur'an are relevant to various physics concepts, such as the solar system, work and energy, fluid dynamics, force, measurement, light, cosmology, thermodynamics, and the structure of the earth. This relevance is demonstrated through the relationship between natural phenomena in the Qur'an and physics concepts such as gravity, Newton's law, Bernoulli's law, the Big Bang theory, and geology. The integration of Quranic verses into physics learning was implemented through the development of learning media, modules, student worksheets (LKPD), physics magazines, and a contextual approach based on Kauniyah verses. This integration had a positive impact on conceptual understanding, learning motivation, critical thinking skills, and strengthening students' religious character. This study concluded that the integration of Quranic verses into physics learning can be a contextual, holistic, and relevant learning approach to support the development of Islamic values-based science education in schools.